Fabrication and Enhancement UV Photodiode Based on Mg-Doped ZnO Nanorods Films - Hameed, Hussein Abdullah; Hassan, J. J.; Saadon, H. L. (Iraqi Journal of Science, 2019)
Magnesium-doped Zinc oxide (ZnO: Mg) nanorods (NRs) films and pure Zinc oxide deposited on the p-silicon substrates were prepared by hydrothermal method. The doping level of the Mg concentration (atoms ratio of Mg to Zn was chosen to be 0.75% and 1.5%. X-ray diffraction (XRD) and energy-dispersive X-ray spectroscopy (EDX) were performed to characterize the prepared films. X-ray diffraction analysis showed a decrease in the lattice parameters of the Mg-doped ZnO NRs. Under 10V applied bias voltage, the responsivity of p-n junction UV photodiode based on pure ZnO and Mg: ZnO with doping ratio (0.75% and 1.5%) was 0.06 A/W and (0.15A/W and 0.27A/W) at UV illumination of wavelength 365 nm respectively, 0.071 A/W and (0.084A/W and 0.11A/W) for UV wavelength of 385 nm with power density 40Î¼W/cm2, respectively. The Mg-doped ZnO NRs photodiode exhibited high photosensitivity, fast response and fall times, and good orientation properties.